Determinants of dispensing antibiotics without prescription by community pharmacists in developing countries: A review - Teressa Andrea Esteves, Gabriel Jay Atabay, Elizabeth Yu Tan (Journal of Applied Pharmaceutical Science, 2023)
Developing countries are more vulnerable to antibiotic resistance and pose the greatest threat to public health globally than developed countries due to complex issues about the nature of their healthcare system as well as other patient-related factors. Inappropriate antibiotic drug use and their unrestricted availability in community pharmacies and other retail establishments can contribute to this issue. The research provides a review of scholarly literature to identify what possible determinants could contribute to inappropriate antibiotic dispensing practices. Most studies in this review have indicated that lack of knowledge among community pharmacists and lax law enforcement, from intrinsic and extrinsic factors, respectively, were the most frequent aspects associated with antibiotic dispensing with no prescription; thus, measures to be taken to counteract or reduce these determinants should be considered. In this case, intervention should be made locally, along with coordination among health authorities and other healthcare providers.
Keywords: Antibiotics, dispensing, community pharmacy, antimicrobial resistance, pharmacists